2008
DOI: 10.1002/14651858.cd006398.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing injuries in the agricultural industry

Abstract: The selected studies provided no evidence that educational interventions are effective in decreasing injury rates among agricultural workers. Financial incentives could reduce injury rates. Legislation to ban pesticides could be effective. Legislation expanding the use of safety devices (ROPS) on new tractors was associated with a decrease in fatal injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 37 publications
3
67
0
Order By: Relevance
“…[3][4][5] Only one of these specifically focused on the child and adolescent population in agricultural settings. 4 The latter noted that the evaluated interventions focused on educational strategies and intermediate outcomes such as knowledge and behavior change.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Only one of these specifically focused on the child and adolescent population in agricultural settings. 4 The latter noted that the evaluated interventions focused on educational strategies and intermediate outcomes such as knowledge and behavior change.…”
Section: Introductionmentioning
confidence: 99%
“…They found that experience rating decreased injuries, an observation that was also reported in another review [31]. It was unclear if introduction of regulation decreased injuries.…”
Section: Resultsmentioning
confidence: 59%
“…Another Cochrane review did not find evidence in three studies that regulatory interventions were effective in construction industry [33]. In again another review, legislation requiring rollover protective structures on new tractors was associated with a decrease in fatal injuries, but the same requirement for existing tractors showed no effect [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of these and other safety features can be addressed, be it through the replacement of older equipment, retrofit programs, financial incentives to improve working conditions, or regulated policy alternatives. 7 Descriptive findings such as those contained in this brief report can help in the establishment of priorities for such prevention initiatives in the agricultural sector. The absence of these safety features, although identified in a Canadian sample of farms from one Prairie province, is likely to be a widespread prevention issue within agricultural populations in Canada and in other countries.…”
Section: Discussionmentioning
confidence: 97%